Kinship Systems, Cooperation, and the Evolution of Culture - Benjamin Enke (Center for Economic Studies and ifo Institute (CESifo), 2018)
An influential body of psychological and anthropological theories holds that societies exhibit heterogeneous cooperation systems that differ both in their level of in-group favoritism and in the tools that they employ to enforce cooperative behavior. According to some of these theories, entire bundles of functional psychological adaptations – religious beliefs, moral values, negative reciprocity, emotions, and social norms – serve as “psychological police officer” in different cooperation regimes. This paper uses an anthropological measure of the tightness of historical kinship systems to study the structure of cooperation patterns and enforcement devices across historical ethnicities, contemporary countries, ethnicities within countries, and among migrants. The results document that societies with loose ancestral kinship ties cooperate and trust broadly, which appears to be enforced through a belief in moralizing gods, individualizing moral values, internalized guilt, altruistic punishment, and large-scale institutions. Societies with a historically tightly knit kinship structure, on the other hand, cheat on and distrust the out-group but readily support in-group members in need. This cooperation regime in turn is enforced by communal moral values, emotions of external shame, revenge-taking, and local governance structures including strong social norms. These patterns suggest that various seemingly unrelated aspects of culture are all functional and ultimately serve the same purpose of regulating economic behavior.
Keywords: D00; O10; 330; Kinship; culture; cooperation; enforcement devices